The effects of saffron consumption on lipid profile, liver enzymes, and oxidative stress in male hamsters with high fat diet - Sina Vakili; Amir Savardashtaki; Mohammad Amin Momeni Moghaddam; Peyman Nowrouzi; Mohammad Khabbaz Shirazi; Ghasem Ebrahimi (Shiraz University of Medical Sciences, 2017)
Saffron (Crocus sativus) is one of the indigenous plants of Iran. Recently its possible effects have been reported on lipid abnormalities and oxidative stress. The aim of this study was to investigate the effects of saffron consumption on lipid profiles, especially the reduction of blood cholesterol, and lipid peroxidation in male hamsters under a high-fat diet. Twenty-six hamster rats were categorized in control group, high-fat diet group (HFD), and high-fat diet group treated with an aqueous saffron extract (HFD+S). The HFD and HFD+S groups were subjected to high-fat diet for 30 days. During last 10 days of this course, the HFD+S group received 100 mg/kg/day saffron through gavage. Saffron administration along with a high fat diet significantly decreased serum levels of total cholesterol, low molecular weight lipoprotein (LDL) cholesterol, malondialdehyde (MDA), and some hepatic enzymes. These results support the possible effects of saffron consumption in the prevention and treatment of cardiovascular disease.